A Analysis of Time and Cost Optimization in Building Contruction Using Time Cost Trade Off Method - Firyaal Nabila (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2023)
The construction of both buildings and roads has several success factors. One of the influencing factors is the timely completion of the project and the costs incurred in accordance with the Budget Plan (RAB) that was prepared during planning. Many projects experience problems with delays in completion time, if the project is completed late then they will be subject to fines. So it is necessary to carry out appropriate calculations so that construction implementation can proceed based on the initial planning. For this reason, this research was carried out by analyzing time and cost optimization using one method, namely Time Cost Trade Off, by calculating the fastest implementation time and the minimum costs incurred. The results obtained from this research are that, by increasing the working hours by 1 hour, the project duration is reduced to 106 days and the cost decreases to Rp. 2,722,750,086, 05. Meanwhile, if workers are added equivalent to an additional 1 hour of working hours, the project duration is reduced to 106 days and costs also decrease to Rp. 2,720,684,806.69. For additional working hours of 3 hours, the project duration becomes 59 days and the cost becomes Rp. 2,552,212,214, 71. Meanwhile, if you add workers equivalent to adding 3 hours of work, the project duration will be 59 days, but the cost will decrease to Rp. 2,545,208,046.33. It can be concluded from this research that by speeding up the project completion time, total costs will decrease and it is most efficient to increase labor rather than increase working hours (overtime). This is done so that the project does not experience delays and incur fines.